PENGARUH MEDIA PEMBELAJARAN BAAMBOOZLE TERHADAP MINAT BELAJAR SISWA DALAM MATERI SISTEM PENCERNAAN MANUSIA KELAS V SDN GORDA 2 - Jihan Hanifah; Aditya Rachman; Ahmad Suganda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by students who have low interest in learning in sciencesubjects, thus the research was conducted. The aim is to determine the effect ofBamboozle learning media on students' interest in learning. This research uses aquantitative approach with a quasi-experimental method. The sample consists oftwo classes, namely the experimental class and the control class. The samplecollection technique in this study uses a purposive sampling technique and theinstrument used in this study is a student learning interest questionnaire withindicators of paying attention in learning, liking the material, enthusiasm, activeparticipation, and learning activity. Data analysis techniques used include normalitytests, homogeneity tests, and independent sample t-tests. The results of the studyshow that there is a significant difference between students' interest in learning inthe experimental class and the control class after learning. This is evidenced by theresults of the t-test which shows a significance value (Sig. 2-tailed) of 0.000 <0.05.Thus, it can be concluded that the use of Bamboozle learning media has a significanteffect on increasing students' interest in learning on the human digestive systemmaterial.